Haematological Response, Performance and Economic Analysis of Cockerel Chicks Fed Enzyme Supplemented Brewer’s Dried Grains Groundnut Cake-based Diets - Isikwenu, J.O.; Udeh, I.; Ifie, I. (Pakistan Journal of Nutrition, 2012)
The effect of replacing Groundnut Cake (GNC) with enzyme supplemented Brewer’s Dried Grains (BDG) at 0, 25, 50, 75 and 100% graded levels in cockerel chicks at 6-11 weeks of age was investigated. Five dietary treatments were formulated to be isonitrogenous and isocaloric to provide 20% crude protein and 2900 kcal/kg metabolizable energy. Two hundred and twenty-five 5 weeks old cockerel chicks (Abor-Acre breed) were randomly allocated to five treatments replicated thrice with 15 cockerels per replicate, fed and watered ad libitum in deep litter pens for 6 weeks. Means of body weight, total weight gain, daily weight gain, feed intake, feed: gain ratio, blood parameters and economic assessment of cockerels fed the control diet, 25 and 50% enzyme supplemented brewer’s dried grains diets were significantly (p<0.05) better than those fed 75 and 100% inclusion levels. The use of enzymes supplemented BDG was more profitable than GNC in cockerel’s diets when the replacement do not exceed the 50% level. Mortality ranged from 1.95-3.56%.